Medullary thyroid cancer as part of MEN 2A (Sipple's syndrome) - Galina A. Batrak; Ekaterina M. Glebova (LLC "MEDIAFORMAT", 2024)
In recent years, increasing attention of researchers has been attracted to the study of multiple endocrine neoplasia (MEN) - neoplastic syndromes affecting two or more endocrine glands. The source of tumors are tissues with embryologically common neuroectodermal origin, related to the APUD system. MEN 2A (Sipple syndrome) includes medullary thyroid carcinoma (97%), hyperparathyroidism (50%) and pheochromocytoma (30%). Descriptions of observations of Sipple syndrome are found quite often in both domestic and foreign literature. However, when analyzing a large number of observations of MEN 2 A, it was found that pheochromocytoma is diagnosed primarily in only 10% of patients, in 50% during examination for medullary cancer, and in 40% in late stages of neoplasia. The presented clinical case of MEN 2A is recommended for study by doctors of various specialties, primarily endocrinologists, therapists and cardiologists.